유두주위오목으로의 망막탈출에 의한 시신경섬유층 결손 1예 - 박재용(Jae Yong Park); 오원혁(Won Hyuk Oh) (Daihan angwa haghoi jabji, 2018)
목적: 녹내장의증으로 경과 관찰하던 환자에서 유두주위오목이 커지면서 그 방향으로 망막이 탈출하여, 시신경섬유층 결손과 함께 연관된 시야장애가 나타난 증례를 경험하였기에 이를 보고하고자 한다. 증례요약: 34세 남자 환자가 녹내장의증으로 본원 녹내장 클리닉으로 의뢰되었다. 환자의 안압은 우안 15 mmHg, 좌안 14 mmHg였다. 굴절이상은 구면렌즈대응치로 우안 -12.75디옵터, 좌안은 -11.50디옵터였으며, 안축장은 우안 28.70 mm, 좌안 28.15 mm였다. 빛간섭단층촬영에서 망막신경섬유층의 두께는 양안 모두 정상 범위 안에 있었다. 양안에서 유두주위오목이 관찰되었으며, 최대수평직경은 우안 155 μm, 좌안 625 μm였다. 2년 뒤 시행한 빛간섭단층촬영에서 우안 유두주위오목은 239 μm로 커지면서 그 방향으로 망막이탈출하여 시신경섬유층결손 및 이에 상응하는 시야장애가 발생하였다. 하지만 좌안 유두주위오목에는 변화가 없었다. 결론: 유두주위오목이 있는 녹내장 또는 녹내장의증 환자에서 유두주위오목 방향으로 시신경섬유층결손이 발생할 수 있으므로 면밀한 경과관찰이 필요하다. Purpose: To report a case of glaucoma suspect with peripapillary pit, which enlarged in size with retinal herniation through the pit, and resulted in retinal nerve fiber layer defect and corresponding visual field defect. Case summary: A 34-year-old male was referred to our glaucoma clinic for glaucoma evaluation. The intraocular pressure was 15 mmHg in the right eye and 14 mmHg in the left eye. The refractive error in spherical equivalence was -12.75 diopters (D) in the right eye and -11.50 D in the left eye. The axial length was 28.70 mm in the right eye and 28.15 mm in the left eye. On optical coherence tomography (OCT), the retinal nerve fiber layer thickness was within normal limits in both eyes. A peripapillary pit was found in both eyes, which measured 155 μm in the right eye and 625 μm in the left eye in maximal horizontal diameters. Two year follow-up OCT images showed that the peripapillary pit in the right eye enlarged to 239 μm and retinal herniation occurred through the pit, resulting in a retinal nerve fiber layer defect and a corresponding visual field defect. However, the peripapillary pit in the left eye had no significant change. Conclusions: Glaucoma patients or suspects, with peripapillary pits need close observation because of the possibility of a retinal nerve fiber layer defect in the direction of the pit. KCI Citation Count: 0